(untitled) (Research, Society and Development, 2021)
The pandemic period brought numerous social and academic changes abruptly to medical education. The aim of this study was to assess the impact that the pandemic had on the education of medical students. This is an analytical cross-sectional study with a quantitative approach. Two questionnaires were applied, one with sociodemographic, personal, and academic data and the other was the Continuum Mental Health Scale, reduced version (MHC-SF) for adults. The survey included 274 medical students, of whom (63.5%) were female and (36.5%) male. Most participants were aged between 21 and 25 years (58.4%). Worst scores of mental health status were identified in females, in students from 1st to 4th period, by those who claimed to have no religion, who did not perform extracurricular activities, did not meet friends, did not exercise, who had a diagnosed psychiatric illness , who had insomnia, who were not satisfied with their academic performance and who had already thought about dropping out of medical school. The present study revealed several factors associated with the mental health condition of medical students during the Covid-19 pandemic period. Furthermore, it exposes the emotional, social, and psychological damages implied by the measures of social distancing and the adoption of distance learning among students, being essential the adoption of measures to combat and prevent the development of this mental health condition.